ANTHROPOGENIC PB ACCUMULATION IN FOREST SOILS FROM LAKE CLAIR WATERSHED: DUCHESNAY EXPERIMENTAL FOREST (QUÉBEC, CANADA) - Ndzangou S.O.; Richer-LaFLèche M.; Houle D. (My University, 2006)
Mineral soil horizons (Ae, Bhf1, Bhf2, Bf, BC and C) were carefully collected from two podzolic soil profiles in the Lake Clair watershed (Québec) in order to assess anthropogenic trace metal accumulation. Petrographic and selective analyses were performed to establish the soil mineralogy and properties. Furthermore, a complete sequential extraction procedure has been applied to help understanding the complex chemical speciation of Pb in forest soils. Chemical speciation of Pb showed a strong vertical gradient: 85% of this metal is mainly partitioned in refractory minerals in the C-horizon whereas in the upper Bhf1 and Ae-horizons, less than 50% of Pb is associated with this fraction. In the Ae-horizon, for example, 35%, 30% and 12% of total Pb, respectively, is associated with the exchangeable, labile organic matter and amorphous Fe-Mn oxides fractions. The distribution of Pb and Cr in the studied forest soils mainly reflects progressive contamination of the watershed by anthropogenic atmospheric sources. The anthropogenic source is indicated by elevated Cr and Pb concentrations in the topsoil (Bhf and Ae) horizons and by strong negative correlation between 206Pb/207Pb ratios and total Pb concentrations. According to these isotopic values, penetration of anthropogenic Pb does not exceed 10 cm in both soil profiles. Below this depth, both Pb concentrations and isotopic ratios remain nearly constant and similar to values observed in pre-anthropogenic sediments from Lake Clair. These values are interpreted as the natural geochemical backgrounds of the watershed. Based on that behaviour, calculated anthropogenic Pb net inputs amounted to between 1.24 and 1.8 g/m2. © 2006 Elsevier Ltd. All rights reserved.